Kinerja Pegawai Tata Usaha SMA Negeri Keberbakatan Olahraga Provinsi Bengkulu - Mustika, Yola; Saputra, Harius Eko; Maryaningsih, Maryaningsih; Kader, Bando Amin C. (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
Organizational performance is a crucial factor in effective resource utilization and strategic decision making that supports growth. Performance evaluation includes comparison with internal and external standards and peer organizations. Factors such as managerial skills, work system effectiveness, motivation, and employee job satisfaction play a significant role in achieving organizational goals. Factors such as managerial skills, work system effectiveness, motivation, and employee job satisfaction play a significant role in achieving organizational goals. Quality service in education contributes to customer satisfaction and achievement of educational goals. School administration has crusial role as administrative services, plays an important role in supporting the educational process. This study was used a qualitative method with a critical paradigm and data was collected through observation, interviews and documentation. This study evaluated the performance of administrative staff at SMA Keberbakatan Olahraga (Sports Talent High School) in Bengkulu Province by focusing on six main indicators: work quality, work quantity, timeliness, effectiveness, and commitment. The study found that the quality of work of administrative staff at this school was very good, characterized by neat and timely administration management. Although there was a slight delay in collecting some documents, overall administration management met the established standards. The high quantity of work reflects the productivity of administrative staff who demonstrate significant commitment to their duties. Despite slight delays in the submission of some documents, the overall administration management meets the established standards. The high quantity of work reflects the productivity of the administration staff who demonstrate significant commitment to their duties. High work quantity reflects the productivity of administrative staff who demonstrate significant commitment to their duties. Timeliness in completing administrative tasks is also considered high, contributing positively to the smooth operation of the school. Effectiveness in resource use was enhanced through effective communication between staff, which supports coordination and achievement of school goals. Employee commitment was supported by training and development programs, although there is a need for improvement in work facilities. Overall, the performance of administrative staff at this high school is very good, playing an important role in supporting the smooth running of school activities and achieving the set educational goals..